Begründen und Erklären im antiken Denken: Akten des 7. Kongresses der Gesellschaft für antike Philosophie 2022 - Becker, Alexander; Becker, Matthias; Bjelde, Joseph; Brüllmann, Philipp; Damiani, Vincenzo; Detel, Wolfgang; Ferro, Antonio; Föllinger, Sabine; Föllinger, Sabine; Gödde, Susanne; Jansen, Ludger; Kazmierski, Sergiusz; et al. (De Gruyter, 2025)
Ancient philosophy developed different, influential modes of justifying and explaining, which the chapters in this volume investigate. They are guided by questions like: How do arguments in ancient philosophical and scholarly texts proceed? Where and why do they integrate forms of non-scholarly explanation? What is the relationship between narrative forms and discursive forms of explanation?
Keywords: Konferenzschrift; Aufsatzsammlung; Geschichte; Antike; Erklärung; Argumentation